Fine‐Tuning of Lewis Acidity: The Case of Borenium Hydride Complexes Derived from Bis(phosphinimino)amide Boron Precursors. Issue 31 (28th June 2016) - Jaiswal, Kuldeep; Prashanth, Billa; Singh, Sanjay
Abstract: Reactions of bis(phosphinimino)amines LH and L′H with Me2 S⋅ BH2 Cl afforded chloroborane complexes LBHCl (1 ) and L′BHCl (2 ), and the reaction of L′H with BH3 ⋅ Me2 S gave a dihydridoborane complex L′BH2 (3 ) (LH=[{(2, 4, 6‐Me3 C6 H2 N)P(Ph2 )}2 N]H and L′H=[{(2, 6‐ i Pr2 C6 H3 N)P(Ph2 )}2 N]H). Furthermore, abstraction of a hydride ion from L′BH2 (3 ) and LBH2 (4 ) mediated by Lewis acid B(C6 F5 )3 or the weakly coordinating ion pair [Ph3 C][B(C6 F5 )4 ] smoothly yielded a series of borenium hydride cations: [L′BH] + [HB(C6 F5 )3 ] − (5 ), [L′BH] + [B(C6 F5 )4 ] − (6 ), [LBH] + [HB(C6 F5 )3 ] − (7 ), and [LBH] + [B(C6 F5 )4 ] − (8 ). Synthesis of a chloroborenium species [LBCl] + [BCl4 ] − (9 ) without involvement of a weakly coordinating anion was also demonstrated from a reaction of LBH2 (4 ) with three equivalents of BCl3 . It is clear from this study that the sterically bulky strong donor bis(phosphinimino)amide ligand plays a crucial role in facilitating the synthesis and stabilization of these three‐coordinated cationic species of boron. Therefore, the present synthetic approach is not dependent on the requirement of weakly coordinating anions; even simple BCl4 − can act as a counteranion with borenium cations. The high Lewis acidity of the boron atom in complex8 enables the formation of an adduct with 4‐dimethylaminopyridine (DMAP), [LBH⋅ (DMAP)] + [B(C6 F5 )4 ] − (10 ). The solid‐state structures of complexes1, 5, and9 were investigated by means of single‐crystal X‐ray structural analysis. Abstract : Let's ionize : A series of stable borenium hydride complexes bonded with sterically bulky bis(phosphinimino)amides have been isolated in a facile manner by adopting Lewis acid‐mediated hydride abstraction or hydride–chloride exchange followed by chloride abstraction from the precursors (see scheme).